EFFECTS OF SHOOTING PERIOD, TIMES WITHIN SHOOTING PERIODS AND PROCESSING SYSTEMS ON THE EXTRACT, CAFFEINE AND CRUDE FIBER CONTENTS OF BLACK TEA - OZDEMIR, F; GOKALP, HY; NAS, S (SPRINGER VERLAG, 1993)
The extract, caffeine and crude fibre contents of black tea, from different shooting periods, different times within each shooting period and processed by five different commercial rolling methods, were examined. The extract and crude fibre contents of black tea were significantly (P < 0.01) affected by all these factors and their interactions. The caffeine content of black tea was affected by the shooting period and times within the shooting period. It was determined that processing methods did not have a significant (P < 0.05) effect on the caffeine content. The amount of extract and caffeine decreased from the first shooting period to the third, and also from the beginning of each shooting period to the end. However, the crude fibre content of the black tea increased, especially from the beginning of each shooting period to the end of each shooting period.
Keywords: CHEMICAL-COMPOSITION; PLUCKING STANDARDS; CAMELLIA-SINENSIS; ORTHODOX; QUALITY; INDIA; Food Science & Technology